3-cerro y 4-mundo: los números del banquete en las ofrendas quechuas - Lorente Fernández, David (2010)
The Quechua offerings in the South of Peru are banquets dedicated to the Pachamama and the Apus, and at the same time, are elaborated mathematical systems controlled by sophisticated operations. Using two principal numbers, 3 and 4, the religious specialist is capable of transmitting polysemic messages. Through the number 3, the religious specialist refers to the people, landscapes and mountains, in sum, to «persons» able to interact among themselves. The number 3 appears in the k’intus, composed of coca leaves, also in the prayers said during the process of the offering ritual. On the contrary, the number 4 does not indicate relationships but spatial forms: it is a geometrical operator that is constructed of the ceremonial square napkin (unk’uña) and paper in which the offering is completely wrapped to make the offering a miniature world, containing the «four directions of the world.» Using these numbers, the religious specialist can recreate the cosmos, establish covenants with the gods and define new situations favorable to the life of Quechuas.